2018
DOI: 10.1074/jbc.m117.797936
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the FliF–FliG complex from Helicobacter pylori yields insight into the assembly of the motor MS–C ring in the bacterial flagellum

Abstract: The bacterial flagellar motor is a self-assembling supramolecular nanodevice.Its spontaneous biosynthesis is initiated by the insertion of the MS ring protein FliF into the inner membrane, followed by attachment of the switch protein FliG. Assembly of this multiprotein complex is tightly regulated to avoid nonspecific aggregation, but the molecular mechanisms governing flagellar assembly are unclear. Here, we present the crystal structure of the cytoplasmic domain of FliF complexed with the Nterminal domain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 29 publications
3
53
0
1
Order By: Relevance
“…FliG N is involved in the interaction with the C-terminal cytoplasmic domain of FliF (FliF C ) ( Fig. 2 B) [ 24 , 25 ]. Inter-molecular interactions between FliG N and FliG N and between FliG M and FliG CN are responsible for the assembly of FliG into the ring structure on the cytoplasmic face of the MS ring [ [26] , [27] , [28] , [29] ].…”
Section: Structure Of the C Ringmentioning
confidence: 99%
“…FliG N is involved in the interaction with the C-terminal cytoplasmic domain of FliF (FliF C ) ( Fig. 2 B) [ 24 , 25 ]. Inter-molecular interactions between FliG N and FliG N and between FliG M and FliG CN are responsible for the assembly of FliG into the ring structure on the cytoplasmic face of the MS ring [ [26] , [27] , [28] , [29] ].…”
Section: Structure Of the C Ringmentioning
confidence: 99%
“…4A ). We focused effort on coevolution analysis of the FliG N-terminal (FliG_N) domain, which is known to adopt multiple folds due to conformational changes triggered by association with FliF C-tail 29 , 30 , 42 . We started with analysis of the FliF C-tail .…”
Section: Resultsmentioning
confidence: 99%
“…maritima or H . pylori FliG_N domains show that FliG_N alters conformation to co-fold with a C-terminal segment of FliF (FliF C-tail ); the resulting complex adopts a conformation similar to that of FliG_M 29 , 30 . Type III injectisome proteins form membrane scaffolds with morphologies similar to the MS ring 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori requires directional motility, mediated by 1 to 6 polar flagella and multiple chemotaxis receptors, to colonize the stomach. Two studies focused on how the flagellar motor complex C‐ring is built . Xue et al identified the structure of a complex containing an N‐terminal fragment of FliG with FliF, revealing an extended superhelical structure with extensive hydrophobic contacts.…”
Section: Helicobacter Pylori Gastric Colonizationmentioning
confidence: 99%